Factors influencing local government financial sustainability: an empirical study. - Rodríguez Bolívar, Manuel Pedro; Navarro Galera, Andrés; Alcaide Muñoz, Laura; López-Subires, María Deseada (Lex localis, 2014)
In the present context of international public finance crisis, the analysis of government sustainability is considered of vital importance, and a significant element in this is the accounting measurement of intergenerational equity. The aim of this paper is to identify factors that may influence the financial sustainability of local government, doing so through the analysis of 116 local administrations in Spain. Based on Pearson correlation analysis, our main findings show that the annual budget result is a key determinant of local government financial sustainability, and highlight the value of controlling the balance of budget expenditures in preventing future problems of viability for these local authority services.
This is an Accepted Manuscript of an article published by LEX LOCALIS-JOURNAL OF LOCAL SELF-GOVERNMENT on 2014, available online: https://doi.org/10.4335/12.1.31-54(2014)
Keywords: Administración local - Aspectos económicos; Financial sustainability; Local governments